Urban regeneration and urban fabrics in Australian cities - Thomson, G.; Newton, P.; Newman, Peter (Henry Stewart Publications, 2016)
© 2017 Henry Stewart Publications. All Right Reserved. This paper describes Australian urban regeneration in terms of urban fabric — walking, transit or automobile, and geography — brownfield and greyfield arenas. Case studies are used to highlight the importance of understanding urban fabric when considering development and regeneration across any geography. Urban regeneration in Australian cities has been occurring in brownfields locations for the past three decades, initially driven by government intervention, but now a strong market force. The ‘peak car’ phenomenon is now associated with an even stronger demand for urban regeneration stretching beyond the inner city into the middle suburbs or greyfields. This paper provides a brief history of major regeneration influences followed by an overview of the processes, policies and practices that can enable the next phase of urban regeneration in all three urban fabrics, particularly the greyfields.